Assessments on Two Mansions and One Identic Pediment in Pasabahce - Kaya, Z. Sena Gunes; Balcan, Cem (Istanbul Univ, Research Inst Turkology, Dept Art History, 2021)
Pasabahce, a Bosphorus village on the Anatolian Side, was originally a Greek settlement. Muslims began to settle there in the second half of the 18th century. The centre of Pasabahce, on the shore, has a texture of attached structures. In the surroundings, many wooden houses and mansions which are located in large gardens, shape the settlement. The mansions are thought to have been used as summer houses by senior government officials. Two mansions located at Sunaziri Street and Sekerpare Street in Pasabahce are the subject of this article. Despite the uncertainty of the construction dates of the two mansions, it is estimated that they were built in the mid-19th century. Considering the construction dates, they are probably two of the oldest existing structures in Pasabahce. The mansions are in very good condition thanks to continuous use. The most remarkable elements of both mansions are the semi-circular shaped and ornamented pediments. The pediments are not the only similarity. Despite their size difference is evident, the mansions also show similar characteristics in terms of planning, materials, ornamental program and spatial use. Just as the proximity of the construction dates are similar, both mansions are estimated to have changed owners and underwent extensive renovation and modification nearly a hundred years ago. The very similarity of the interventions in the extensive renovation and modification process, strengthens the relation between mansions throughout the historical process.
Paşabahçe’deki İki Köşk ve Ortak Bir Alınlığın Düşündürdükleri
Keywords: Beykoz; Pasabahce; Mansion; Traditional Architecture; Bosphorus